Analytical and Numerical Study of Steady Flow of Thermo-Viscous Fluid Between Two Horizontal Parallel Plates in Relative Motion - Pothanna, N.; Aparna, P.; Sireesha, G.; Padmaja, P. (Communications in Mathematics and Applications, 2022)
In the present paper we examined the Analytical and Numerical study of steady flow of thermo viscous fluid between two parallel horizontal plates in relative motion. The numerical solutions of governing equations of flow involving velocity and temperature have been obtained using 6th order R-K methods via MATHEMATICA ND solver. The governing equations of the flow also have been solved analytically. The numerical solutions for different values of the physical parameters like thermal stress interaction material coefficient, thermo conductivity parameter and the porosity coefficient have been presented in terms of tables and illustrated graphically. The results for linearized steady incompressible motion fluid flow in between two non-porous parallel horizontal plates also obtained both numerically and analytically. The numerical and analytical results are compared and are verified to be in good convergence. The solutions of the present investigation will definitely give an excellent perception of nuclear, industrial and clinical applications.